Spectral Analysis of Estuarine Water for Characterisation of Inherent Optical Properties and Phytoplankton Concentration - Marrable, Daniel Stephen (Curtin University, 2018)
In this study, a hyperspectral radiometer was used to measure the remote sensing reflecance continuously along the Swan-Canning Cleanup Programe (SCCP) water sampling sites. The results of this thesis show that the model and method used in this study are capable of accurately estimating the phytoplankton concentration in the Swan River for a continuous transect encompassing and connecting half of the SCCP sample locations up to, and including Nile Street.